TEMPERATURE INFLUENCE ON THE GELATION PROCESS OF TETRAETHYLORTHOSILICATE USING SOL-GEL TECHNIQUE - Twej, Wesam (Iraqi Journal of Science, 2024)
In this work the gelling time of silica alkoxide obtained by sol-gel process has been investigated. The Investigations are made with three variable parameters: water to TEOS molar ratios (1.4, 2, and 10), different pH values and reaction temperatures (25, 40 and 55 ◦C). The study shows that, the reaction temperatures have different effects on the gelling time according to other sol-gel preparation parameters. The values of the activation energy (Ea) were estimated to be approximately the same in the studied range of initial hydrolysis ratio 1.4, 2, 10, slightly varying around 21.2 kJ.mol-1, when the recipes derived under tightly closed cover. While under open recipe and with R-ratio equal to 1.4, Ea rises to 37.2 kJ.mol-1.